mutiplying radicals

Discussion in 'Homework Help' started by zelda1850, Nov 13, 2010.

  1. zelda1850

    Thread Starter New Member

    Jan 3, 2010
    18
    0
    am i doing these questions correctly can someone check

    1) 3\sqrt{3}(4-3\sqrt{5})

    3\sqrt{3} * (4) = 12\sqrt{3}
    3\sqrt{3} * (3\sqrt{5} = 9\sqrt{15})

    = 12\sqrt{3} - 9\sqrt{15}


    2) 4\sqrt{15}(-3\sqrt{6} + 5)

    4\sqrt{15} * (-3\sqrt{6} = 12\sqrt{90})
    4\sqrt{15} * (5) = 20\sqrt{15}

    12\sqrt{90} + 20\sqrt{15}


    3) \sqrt{-2} (\sqrt{10} - 4\sqrt{6}

    \sqrt{-2} * \sqrt{10} = \sqrt{-20}
    \sqrt{-2} * 4\sqrt{6} = 4\sqrt{-12}

    = \sqrt{-20} - 4\sqrt{-12}

    4) (\sqrt{2a} - 5)(7\sqrt{2a} - 5)

    -5 * -5 = -25
    -5 * \sqrt{2a} = -10a

    7\sqrt{2a} * -5 = -35 \sqrt{2a}
    7\sqrt{2a} * 2a = 7\sqrt{2a}

    and then i got stuck

    5) (7+ \sqrt{6})(1 + \sqrt{6})

    \sqrt{6} * \sqrt{6} = \sqrt{36}
    \sqrt{6} * 7 = 7\sqrt{-12}

    1 * \sqrt{6} = \sqrt{6}
    1 * 7 = 7

    = 7 + 7\sqrt{6} + \sqrt{36}
     
    Last edited: Nov 13, 2010
  2. mik3

    Senior Member

    Feb 4, 2008
    4,846
    63
    1) correct

    2) sign error

    3) correct

    4) wrong

    5) wrong
     
Loading...
Related Forum Posts:
  1. zelda1850
    Replies:
    2
    Views:
    1,149